Effect of Bank Competition on Financial Stability: Empirical Evidence from Nepal - G.C., Surya Bahadur; Sharma, Gyaneswar (Economic Literature, 2018)
There are two hypotheses about the relationship between competition and financial stability in the banking system: “competition-fragility” view argues that competition makes banks more likely totake excessive risks, thereby leading to fragility, while “competition-stability” view suggests that higherinterest rates in less competitive environments may cause borrowers to take higher risks,resulting in higher probability of non-performing loans and a more fragile system. This paper empirically examines the impact of competition on Nepalese banking system employing annual data of commercial banks from 1999 to 2012 period using fixed effects panel data model. The study period represents the era of rapid growth in financial institutions in Nepal. The HHI and n-bank concentration ratios are used as measure of competition while Z-index and nonperforming loans ratioare used as proxies of financial stability. The effects of macroeconomic factors and bank specific indicators are also taken into account. The results reveal that there is apositive relationship between greater banking competition and financial stability in Nepal, supporting the “competition-stability” view. Competition in banking sector is found to result in decrease in credit risk and contribute for financial stability. Mixed results have been achieved incase of the impact of bank competition on overall stability. The findings indicate that both higher concentration and higher competition are detrimental for stability. Hence, policymakers should facilitate further consolidation in the financial industry, however, it should be ensured that excessive consolidation doesn’t result in an environment that hinders competition. In addition,besides competition level in the banking system, macroeconomic situation of the country is found to be an important determinant of banking system stability. Economic Literature, Vol. XIII August 2016, page 19-31